ChemInform Abstract: Single Molecule Sensing with Solid‐State Nanopores: Novel Materials, Methods, and Applications. Issue 16 (28th March 2013) - Miles, Benjamin N.; Ivanov, Aleksandar P.; Wilson, Kerry A.; Dogan, Fatma; Japrung, Deanpen; Edel, Joshua B.
Abstract Review: 68 refs.